Study of The Impact of The Incompatibility of Space Utilization In The Krukut River - Mangasi, Kevin Daniel; Marthanty, Dwinanti Rika (UI Scholars Hub, 2023)
The emergence of development on riverbanks has raised environmental problems in Indonesia, such as flooding, one of which is in the Krukut River Basin which crosses the province of DKI Jakarta. The land use change around the Krukut River causes narrowing and disrupts the absorption of rainwater and triggers sedimentation. This study aims to identify risks in the Krukut riverbank area based on the variable area of land use mismatch, population density, frequency and depth of flooding, volume of waste production, availability of waste management for water bodies and waste banks. The method used in this research is to load the score. Based on this research, the priority location is Cipedak Village, Jagakarsa District. It can be seen that at this location there is a narrowing and narrowing of the Krukut watershed. To anticipate this, normalization and construction of plaster can be carried around the banks of the Krukut watershed in the area.